Intergroup Competition as a Double-Edged Sword: How Sex Composition Regulates the Effects of Competition on Group Creativity - Baer, Markus; Vadera, Abhijeet K.; Leenders, Roger T. A. J.; Oldham, Greg R. (Organization Science, 2014)
Building on social role theory, we extend a contingency perspective on intergroup competition proposing that having groups compete against one another is stimulating to the creativity of groups composed largely or exclusively of men but detrimental to the creativity of groups composed largely or exclusively of women. We tested this idea in two separate studies: a laboratory experiment (Study 1) and a field study (Study 2). Study 1 showed that competition had the expected positive effects on the creativity of groups composed mostly or exclusively of men and produced the predicted negative effects on the creativity of groups composed of women, even though the latter effects emerged at the high end of the competition spectrum and for sex-homogeneous groups only. Results of Study 1 also revealed that within-group collaboration mediated the joint effects of competition and sex composition on group creativity. Study 2 replicated the results of Study 1 in a field setting involving research and development teams. We discuss the implications of these findings for theory and practice.